A new species of Strepsodiscus Knight (Gastropoda, Bellerophontoidea) from the upper Cambrian of Argentina - Pinilla, Maria Karina (2008)
Strepsodiscus austrinus sp. nov. (Gastropoda, Bellerophontoidea) from the Lampazar Formation at Angosto de la Quesera locality (Salta Province, Argentina) is described. The new species is characterized by having a laterally compressed smooth shell. The spire is composed of three tangent whorls slightly coiled to the left, and the final 1/4 At whorl free. Strepsodiscus Knight is reported in South America for the first time. The specimens studied were collected in association with trilobites of the Parabolina (Neoparabolina) frequens argentina Zone (uppermost Cambrian). ©2008 E. Schweizerbart'sche Verlagsbuchhandlung.